Genome-wide screening of DNA copy number alterations in cervical carcinoma patients with CGH+SNP microarrays and HPV-FISH - Kuglik, Petr; Smetana, Jan; Vallova, Vladimira; Moukova, Lucie; Kasikova, Katerina; Cvanova, Michaela; Brozova, Lucie (International journal of clinical and experimental pathology, 2014)
Alterations in the genome that lead to changes in DNA sequence copy number are characteristic features of solid tumors. We used CGH+SNP microarray and HPV-FISH techniques for detailed screening of copy number alterations (CNAs) in a cohort of 26 patients with cervical carcinoma (CC). This approach identified CNAs in 96.2% (25/26) of tumors. Array-CGH discovered CNAs in 73.1% (19/26) of samples, HPV-FISH experiments revealed CNAs in additional 23.1% (6/26) of samples. Common gains of genetic sequences were observed in 3q (50.0%), 1q (42.4%), 19q (23.1%), while losses were frequently found in 11q (30.8%), 4q (23.1%) and 13q (19.2%). Chromosomal regions involved in loss of heterozygosity were observed in 15.4% of samples in 8q21, 11q23, 14q21 and 18q12.2. Incidence of gain 3q was associated with HPV 16 and HPV 18 positive samples and simultaneous presence of gain 1q (P = 0.033). We did not found a correlation between incidence of CNAs identified by array-CGH and HPV strain infection and incidence of lymph node metastases. Subsequently, HPV-FISH was used for validation of array-CGH results in 23 patients for incidence of hTERC (3q26) and MYC (8q24) amplification. Using HPV-FISH, we found chromosomal lesions of hTERC in 87.0% and MYC in 65.2% of specimens. Our findings confirmed the important role of HPV infection and specific genomic alterations in the development of invasive cervical cancer. This study also indicates that CGH+SNP microarrays allow detecting genome-wide CNAs and copy-neutral loss of heterozygosity more precisely, however, it may be less sensitive than FISH in samples with low level clonal CNAs.
Keywords: Carcinoma; ztráta heterozygozity; Sensitivity and Specificity; senzitivita a specificita; Humans; lidé středního věku; Oligonucleotide Array Sequence Analysis; In Situ Hybridization, Fluorescence; Female; Aged; dospělí; nádory děložního čípku; Loss of Heterozygosity; DNA Copy Number Variations; senioři; lidé; srovnávací genomová hybridizace; karcinom; Adult; Papillomavirus Infections; ženské pohlaví; hybridizace in situ fluorescenční; Middle Aged; stanovení celkové genové exprese; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; infekce papilomavirem; variabilita počtu kopií segmentů DNA; Uterine Cervical Neoplasms; Gene Expression Profiling; Comparative Genomic Hybridization